High accuracy of home-based community rapid HIV testing in rural Malawi - MOLESWORTH, Anna M (2010)
OBJECTIVE: To assess the performance of rapid HIV antibody tests when used as part of a home-based community-wide counselling and testing strategy in northern Malawi. DESIGN: A cross-sectional population survey of HIV infection, 2007-2008. METHODS: Adults aged 15 or over in a demographic surveillance area were counselled and then offered an HIV test at their home by government certified counsellors. Two initial rapid tests (Detemine™ and Uni-Gold™) were performed on all samples, and a third, tie-breaker test (SD Bioline) used to resolve discordant results. All people who wanted to know were post-test counselled and informed of their results, with referral to local clinical services if found to be HIV positive. Laboratory quality control comprised re-testing all positive and every tenth negative venous blood sample collected. RESULTS: A total of 10819 adults provided venous blood samples for HIV-testing, of whom 7.5% (813) were HIV positive. The accuracy of the parallel testing strategy used was high, with 99.6% sensitivity, 100.0% specificity, 99.9% positive predictive value and 99.9% negative predictive values. CONCLUSION: Face-to-face rapid testing by health personnel with minimum training, at the clients’ home performs well when used on a wide scale in the community setting.